ChemInform Abstract: Enantioselective Copper Catalyzed C—H Insertion Reaction of 2‐Sulfonyl‐2‐diazoacetamides to Form γ‐Lactams. Issue 9 (March 2015) - Clarke, Leslie Ann; Ring, Aoife; Ford, Alan; Sinha, Abhijeet S.; Lawrence, Simon E.; Maguire, Anita R.
Abstract The first example of asymmetric Cu‐catalyzed intramolecular C—H insertion reaction of title compounds (I) is described.